Arbidol combined with LPV/r versus LPV/r alone against Corona Virus Disease 2019: A retrospective cohort study. Issue 1 (July 2020) - Deng, Lisi; Li, Chunna; Zeng, Qi; Liu, Xi; Li, Xinghua; Zhang, Haitang; Hong, Zhongsi; Xia, Jinyu
Highlights: Patients were given oral arbidol and LPV/r in the combination group and oral LPV/r only in the monotherapy group for 5–21 days. Our study shows that oral arbidol and LPV/r in the combination group is associated with a significant elevated negative conversion rate of coronavirus' test in 7-day and 14-day, compared with LPV/r only in the monotherapy group. Combination therapy is associated with a significantly improved the chest CT scans in 7-day. We suppose that reducing the viral load as soon as possible could benefit the delay of the progression of lung lesions. Summary: Background: Corona Virus Disease 2019 (COVID-19) due to the 2019 novel coronavirus (SARS-CoV-2) emerged in Wuhan city and rapidly spread throughout China. We aimed to compare arbidol and lopinavir/ritonavir(LPV/r) treatment for patients with COVID-19 with LPV/r only. Methods: In this retrospective cohort study, we included adults (age≥18years) with laboratory-confirmed COVID-19 without Invasive ventilation, diagnosed between Jan 17, 2020, and Feb 13, 2020. Patients, diagnosed after Jan 17, 2020, were given oral arbidol and LPV/r in the combination group and oral LPV/r only in the monotherapy group for 5–21 days. The primary endpoint was a negative conversion rate of coronavirus from the date of COVID-19 diagnosis(day7, day14), and assessed whether the pneumonia was progressing or improving by chest CT (day7). Results: We analyzed 16 patients who received oral arbidol and LPV/r in the combination group and 17 who oral LPV/r only in the monotherapy group, and both initiated after diagnosis. Baseline clinical, laboratory, and chest CT characteristics were similar between groups. The SARS-CoV-2 could not be detected for 12(75%) of 16 patients' nasopharyngeal specimens in the combination group after seven days, compared with 6 (35%) of 17 in the monotherapy group ( p < 0·05). After 14 days, 15 (94%) of 16 and 9 (52·9%) of 17, respectively, SARS-CoV-2 could not be detected ( p < 0·05). The chest CT scans were improving for 11(69%) of 16 patients in the combination group after seven days, compared with 5(29%) of 17 in the monotherapy group ( p < 0·05). Conclusion: In patients with COVID-19, the apparent favorable clinical response with arbidol and LPV/r supports further LPV/r only.